2008
DOI: 10.1038/nnano.2008.269
|View full text |Cite
|
Sign up to set email alerts
|

Spatial periodicity in molecular switching

Abstract: The ultimate miniaturization of future devices will require the use of functional molecules at the nanoscale and their integration into larger architectures. Switches represent a prototype of such functional molecules because they exhibit characteristic states of different physical/chemical properties, which can be addressed reversibly. Recently, various switching entities have been studied and switching of single molecules on surfaces has been demonstrated. However, for functional molecules to be used in a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
170
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 20 publications
5
170
1
2
Order By: Relevance
“…30 Further, derivatives were considered in which two tert-butyl groups of TBA were replaced by -COOH groups, i.e., 3,5-ditert-butyl-3,5′-dicarboxyl-AB (DBDCA), 31 or in which two of the four tert-butyl groups were rearranged, 2,2′,5,5′-tetra-tertbutyl-AB (TBA′)ssee the Supporting Information for details.…”
Section: Computational Methodologymentioning
confidence: 99%
“…30 Further, derivatives were considered in which two tert-butyl groups of TBA were replaced by -COOH groups, i.e., 3,5-ditert-butyl-3,5′-dicarboxyl-AB (DBDCA), 31 or in which two of the four tert-butyl groups were rearranged, 2,2′,5,5′-tetra-tertbutyl-AB (TBA′)ssee the Supporting Information for details.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The study of such systems gives detailed insight into fundamental processes that take place at an organic-inorganic interface. For an in-depth understanding, it is advantageous to use a scanning tunneling microscope (STM) for imaging because it provides information about the local environment of each individual molecule, which is important since the molecular properties might differ locallydue to defects, step edges, or different areas of a surface reconstruction [4,5]. For instance, individual C 60 molecules were found to change between dark and bright appearances in STM images, caused by the diffusion of surface [6] or bulk [7] vacancies, charge transfer between molecule and surface [8], or adsorption on small metal islands [9].…”
mentioning
confidence: 99%
“…[2][3] With a few exceptions, [4][5][6][7] most of these studies have focused on azobenzene derivatives on metal surfaces, where isomerization can be induced by light, [8][9] thermal energy, 9 and the tunneling current [10][11] or the electric field 12 from an STM tip. However, it has been shown that different substrates, 13 different surface orientations, 13 or even different areas of the same surface [14][15] can suppress the isomerization for the same molecules. In a recent report the surface has been suggested to lower the energy barrier for isomerization, but no specific mechanism could be identified.…”
mentioning
confidence: 99%